Improvements in Children's Feeding Behavior after Intensive Interdisciplinary Behavioral Treatment: Comparisons by Developmental and Medical Status. Issue 6 (November 2020) - Seiverling, Laura; Hendy, Helen M.; Yusupova, Stella; Kaczor, Aleksandra; Panora, Julio; Rodriguez, JoKathleen
This study examined changes in child mealtime behavior, diet variety, and family mealtime environment after intensive interdisciplinary behavioral treatment (IIBT) for 52 children referred to a day treatment feeding program. Children fell into three developmental status groups including autism spectrum disorder ( n = 16), other special needs ( n = 19), and no special needs ( n = 17), with some having no known medical problems ( n = 22) and some having gastrointestinal, cardiopulmonary, and/or endocrine-metabolic problems ( n = 28). At pre-intervention and post-intervention, caregivers completed the About Your Child's Eating scale, the Brief Assessment of Mealtime Behavior in Children, and a food preference inventory of 70 common foods (20 fruits, 23 vegetables, 12 proteins, 8 grains, 7 dairy). Mixed-factor 2 × 3 ANOVAs compared each of the 11 feeding outcomes across the two study phases (pre-, post-intervention) for the three developmental status groups. All feeding outcomes except fruit acceptance showed significant improvements from pre- to post-intervention, with no main effects for developmental status, and no interaction effects. Additionally, mixed-factor 2 × 2 ANOVAs compared each of the 11 feeding outcomes across the two study phases (pre-, post-intervention) for children with and without medical problems. All feeding outcomes except fruit acceptance showed significant improvements from pre- to post-intervention, with no main effects for medical status, and no interaction effects. Present results suggest that IIBT is effective for improving a number of children's feeding problems, regardless of their developmental or medical status.